2021
DOI: 10.1038/s41467-020-20495-4
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal antibiotic exposure impairs child growth during the first six years of life by perturbing intestinal microbial colonization

Abstract: Exposure to antibiotics in the first days of life is thought to affect various physiological aspects of neonatal development. Here, we investigate the long-term impact of antibiotic treatment in the neonatal period and early childhood on child growth in an unselected birth cohort of 12,422 children born at full term. We find significant attenuation of weight and height gain during the first 6 years of life after neonatal antibiotic exposure in boys, but not in girls, after adjusting for potential confounders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 54 publications
3
97
2
1
Order By: Relevance
“…Important in this regard is to again note that bifidobacteria or lactobacilli are generally absent in extremely premature children. The abundance, or the diminished abundance in the case of antibiotics [37], of these bacteria is frequently linked with improved growth. Similarly, the use of probiotics in term and preterm infants has been found associated with improved weight gain [38].…”
Section: Discussionmentioning
confidence: 99%
“…Important in this regard is to again note that bifidobacteria or lactobacilli are generally absent in extremely premature children. The abundance, or the diminished abundance in the case of antibiotics [37], of these bacteria is frequently linked with improved growth. Similarly, the use of probiotics in term and preterm infants has been found associated with improved weight gain [38].…”
Section: Discussionmentioning
confidence: 99%
“…Uzan-Yulzari et al recently reported that neonatal antibiotic exposure was associated with reduced growth during the first six years of life particularly in boys, whereas antibiotic use after the neonatal period was associated with excessive childhood weight gain in both genders. These effects were likely mediated by the gut microbiota, specifically the decreased abundance and diversity of bifidobacteria, which remained detectable even 24 months after exposure [85]. Alarmingly, antibiotic exposure during the breastfeeding period may eliminate the beneficial metabolic effects of breastfeeding by altering the gut microbiota [86].…”
Section: Antibioticsmentioning
confidence: 99%
“…In addition to mode of delivery, the antibiotics usage during the pregnancy seems alter both the maternal and neonatal microbiomes which may lead to subsequent allergy diseases in childhood ( 16 , 17 ). Moreover, evidence suggesting that maternal antibiotic usage before and after pregnancy can increase the childhood asthma's risk ( 18 ). Furthermore, it should be noted that child exposed to antibiotics in the first days of life can reduced abundance and diversity of Bifidobacterium species ( 18 ) and increase the abundancy of Enterobacteriaceae species ( 19 ), which may induce the development of asthma.…”
Section: Events In Early Life and Dysbiosis In Asthmamentioning
confidence: 99%
“…Moreover, evidence suggesting that maternal antibiotic usage before and after pregnancy can increase the childhood asthma's risk ( 18 ). Furthermore, it should be noted that child exposed to antibiotics in the first days of life can reduced abundance and diversity of Bifidobacterium species ( 18 ) and increase the abundancy of Enterobacteriaceae species ( 19 ), which may induce the development of asthma. Therefore, it is important to raise the question about the contributions of antibiotics and infection on microbiome disturbance during and after pregnancy, further studies regarding this topic should be address.…”
Section: Events In Early Life and Dysbiosis In Asthmamentioning
confidence: 99%